POTENSI SEED BANK DAN DOMINANSI GULMA PADA LAHAN SEBELUM DAN SETELAH REPLANTING - Prasetyo, Riko; Normagiat, Sigit; Ceri, Bunia (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Oil palm plantations (Elaeis guinensis Jacq.) are the main commodity developed in Indonesia, but from the cultivation aspect, there are weeds that can interfere with productivity. Analysis of weed vegetation and weed seed banks is needed to determine their structure and composition. The problem formulation is knowing the structure of vegetation and the potential for weed seeds on the land before and after replanting. The aim of the research is to determine the structure of weed vegetation and weed seed banks in oil palm plants. The research method used a purposive sampling field survey in the oil palm plantation planting area with a plot size of 1×1 m with a total of 5 plot points in 1 Ha on land before replanting and after replanting aged 2 and 4 years. Take the seed bank on 15 x 15 cm land at a depth of 15 cm at 5 points per plot. Broadleaf weeds are the most dominant both in the weed seed bank variable and in the land before and after replanting, while the most dominant weed in the land before replanting is Davallia denticulata, while in the land after 2 years of replanting the most dominant weed is Nephrolepis biserrata and in the land after replanting 4 The most dominant weed this year was Ageratum conyzooides. The recommendation from this research is that weed control can be carried out using contact herbicides because most of the dominant weeds found on the research land are ferns and broadleaf weeds.